MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI DENGAN PENDEKATAN PERMAINAN SAINTIFIK PADA TK AISYIYAH 1 TALANGPADANG - Hantari, Dewinta Widhi; Yulia, Lian Desi; Hartoni, Hartoni (STIT AL MULTAZAM, 2021)
The purpose of this study was to determine the improvement of fine motor skills in children in the Aisyiyah 1 Talang Padang Kindergarten group. This type of research uses Classroom Action Research which is focused on classroom situations or Classroom Action Research. Data collection tools consist of observation, interviews, job performance tests, documentation. Data analysis techniques by means of data reduction, data display and data verification. By using this analysis, the authors conclude that the results can be seen from an increase in children's fine motor skills, which in the pre-cycle research it can be seen that students who reach the BSH assessment standard are 5 children 25%, MB 7 children are 35%, BB 8 children are 40% of all participants. students totaling 20 students. Then in the first cycle of BSH 7 children 35%, MB 7 children 35% BB 6 children 30% and in the second cycle BSH 11 children 55% MB 5 children 25% BB 4 children 20% and cycle III BSH 16 children 80% MB 4 children 20% BB 0 children 0%.